Building a Network of Academics Who Use, Contribute To and Disseminate, an Online, Cost-Effective Histology Learning and Teaching Resource for Students in Australia and Overseas : Final Report. - Meyer, Geoffrey T. (Australian Learning and Teaching Council (ALTC), 2011)
Final report of a Teaching Fellowship at The University of Western Australia. The research focused on Histology, the study of the microscopic anatomy of cells, tissues and organs of plants and animals. Histology is an essential tool of biology and medicine but providing histology courses, particularly laboratory classes, is becoming increasingly expensive. The Fellowship Program addressed this issue. More cost-effective solutions were achieved through developing an online learning resource which also improved student learning experiences and outcomes.